1997
DOI: 10.1136/bmj.314.7086.1033
|View full text |Cite
|
Sign up to set email alerts
|

Integration of hepatitis B vaccination into national immunisation programmes

Abstract: Hepatitis B is a major public health problem even though safe and effective vaccines have been available for over 10 years. Because hepatitis B infection is largely asymptomatic with long term complications occurring after many years it has not received the attention it deserves. Strategies to immunise those at high risk have failed to control the disease. Delegates to the World Health Assembly of the World Health Organisation recommended in May 1992 that all countries should integrate hepatitis B vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(72 citation statements)
references
References 14 publications
1
65
0
6
Order By: Relevance
“…However, without a complementary infant vaccination strategy, chronic HBV infection that occurs in infancy or early childhood, which accounts for 10% to 15% of all chronic infections in Canada, will not be prevented (45). To strengthen immunization programs in Canada, some jurisdictions (including British Columbia, New Brunswick, the Northwest Territories, Prince Edward Island and the Yukon Territory) have undertaken a universal program which combines infant and preadolescent vaccination (42,46,47).…”
Section: Prevention Of Nosocomial Transmission Of Hbvmentioning
confidence: 99%
“…However, without a complementary infant vaccination strategy, chronic HBV infection that occurs in infancy or early childhood, which accounts for 10% to 15% of all chronic infections in Canada, will not be prevented (45). To strengthen immunization programs in Canada, some jurisdictions (including British Columbia, New Brunswick, the Northwest Territories, Prince Edward Island and the Yukon Territory) have undertaken a universal program which combines infant and preadolescent vaccination (42,46,47).…”
Section: Prevention Of Nosocomial Transmission Of Hbvmentioning
confidence: 99%
“…1,8 Thus, inclusion of the vaccine against HBV in the universal vaccination program has been recommended among the strategies for controlling the infection. [9][10][11] In the United States of America and some European countries, prevention of perinatal transmission by screening for HBsAg in all pregnant women with a history of hepatitis B has also been recommended. These screening programs would allow the timely administration of a vaccine in newborns born to seropositive mothers.…”
mentioning
confidence: 99%
“…The hepatitis B virus (HBV) carrier rate in India is estimated at 4.7%, and HBV carrier load between 37.5 and 42.5 million. 4 In a study conducted by WHO, it was found that in the year 2006 alone, there was 2472 cases of Diphtheria, 2587cases of tetanus, and 22 616 cases of Pertussis. 5 The estimated annual incidence of Hib infection in Indian children (age <5 y) is 50-60 per 100 000 of which 7.6% infected are infants (<1 y of age).…”
Section: Scope and Needmentioning
confidence: 99%